The baby plan : a novel - Rorick, Kate, 1978-; OverDrive, Inc. (New York, NY : William Morrow, an imprint of HarperCollinsPublishers, 2018)
Nathalie Kneller: Nathalie's plan: to announce her pregnancy now that she's finally made it past twelve weeks! But just as she's about to deliver (so to speak) the big news to her family, her scene-stealing sister barfs all over the Thanksgiving centerpiece. Yup, Lyndi's pregnant too, swiping the spotlight once more... Lyndi Kneller: Lyndi's plan: finally get her life together! She's got a new apartment, new promotion, new boyfriend. What she didn't count on--a new baby! She can barely afford her rent, much less a state-of-the-art stroller... Sophia Nunez: Sophia's plan: Once she gets her daughter Maisey off to college, she'll finally be able to enjoy life as make-up artist to one of Hollywood's biggest stars, and girlfriend to one of rock's hottest musicians. But after 18 years she discovers the stork is once again on its way... Now these women are about to jump headlong into the world of modern day pregnancy. It's a world of over the top gender reveal parties (with tacky cakes and fireworks); where every morsel you eat is scrutinized and discussed; where baby names are crowd-sourced and sonograms are Facebook-shared. And where nothing goes as planned...
Nathalie Kneller is set announce her pregnancy when her scene-stealing sister Lyndi barfs all over the Thanksgiving centerpiece. Lyndi's finally getting her life together, but didn't count on a baby; she can barely afford her rent. Sophia Nunez knows once she gets her daughter Maisey off to college, she'll finally be able to enjoy career as a make-up artist, and as girlfriend to one of rock's hottest musicians-- until she finds out she's pregnant. Welcome to the world of modern day pregnancy, where baby names are crowd-sourced, sonograms are Facebook-shared... and where nothing goes as planned!
"P.S. insights, interviews & more..."--Cover.
Electronic book.
Electronic reproduction.
Keywords: Advantage title -- Fiction; Pregnant women -- Fiction; Sisters -- Fiction; FICTION / Family Life; FICTION / Women; Pregnant women; Sisters; Domestic fiction; Fiction; Domestic fiction; Electronic books